TRANSFER OF ACQUIRED COMPETENCIES IN THE SCIENTIFIC SCHOOL OF THE MILITARY SCIENTIFIC DIVISION (ORGANIZATION) - Ryzhykov, V.; Horiacheva, K.; Kravchenko, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2022)
The essence of the concepts: scientific school and scientific community; the order of implementation of scientific thought within these formations is thoroughly considered; the methodology carrying out the transfer of competencies in military scientific divisions (collectives) was determined. The key person in a scientific school is its leader (he gives the name of the school). It is usually an excellent, authoritative scientist who generates ideas (new directions of research); a scientist who can unite other like-minded people around him or her. In a military scientific division, it is also a researcher. Generally, the position of chief researcher – responsible for a particular branch of scientific study in the research department, the center. A scientific school of the military scientific team is a creative team of researchers of different generations, united by a common program and style of research work, acting under the guidance of a recognized leader, a well-known scientist in the field of military science. Each scientific school has at least three Doctors of Science in one field of study. The most common method of identifying the transfer of acquired competencies by a researcher in a scientific school of a military scientific division is to study the course of PhD and doctoral dissertations of the scientists who are members of this informal collective. It is effective because it provides concrete results based on quantitative data on the theses defended under the guidance of a particular scholar. And it also shows that the topics of the students' dissertations correspond to the leader's dissertation (scientific search). This method is simple and reduces the tasks of identifying the transfer of acquired competencies by a researcher to the establishment of formal characteristics. By identifying the document flows it is possible to study the content unity of the problems of a scientific school. Bibliometric methods help to study the frequency of citation of the works of the leader of the scientific school.
Keywords: science school, transfer, active pedagogical activity, paradigm, military scientific division, cooperation of scientists, transversal competence